The Impact of Vedolizumab on Pre-Existing Extraintestinal Manifestations of Inflammatory Bowel Disease: A Multicenter Study. Issue 8 (9th November 2020) - Ramos, Guilherme Piovezani; Dimopoulos, Christina; McDonald, Nicholas M; Janssens, Laurens P; Hung, Kenneth W; Proctor, Deborah; Ruggiero, Elizabeth; Kane, Sunanda; Bruining, David H; Faubion, William A; Raffals, Laura E; Loftus, Edward V; et al.
Abstract: Background: There are limited data on how vedolizumab (VDZ) impacts extraintestinal manifestations (EIMs) in inflammatory bowel disease (IBD). The aim of this study was to determine the clinical outcomes of EIMs after initiation of VDZ for patients with IBD. Methods: A multicenter retrospective study of patients with IBD who received at least 1 dose of VDZ between January 1, 2014 and August 1, 2019 was conducted. The primary outcome was the rate of worsening EIMs after VDZ. Secondary outcomes were factors associated with worsening EIMs and peripheral arthritis (PA) specifically after VDZ. Results: A total of 201 patients with IBD (72.6% with Crohn disease; median age 38.4 years (interquartile range, 29-52.4 years); 62.2% female) with EIMs before VDZ treatment were included. The most common type of EIM before VDZ was peripheral arthritis (PA) (68.2%). Worsening of EIMs after VDZ occurred in 34.8% of patients. There were no statistically significant differences between the worsened EIM (n = 70) and the stable EIM (n = 131) groups in term of age, IBD subtype, or previous and current medical therapy. We found that PA was significantly more common in the worsening EIM group (84.3% vs 59.6%; P < 0.01). Worsening of EIMs was associated with a higher rate of discontinuation of VDZ during study follow-up when compared with the stable EIM group (61.4% vs 44%; P = 0.02). Treatment using VDZ was discontinued specifically because of EIMs in 9.5% of patients. Conclusions: Almost one-third of patients had worsening EIMs after VDZ, which resulted in VDZ discontinuation in approximately 10% of patients. Previous biologic use or concurrent immunosuppressant or corticosteroid therapy did not predict EIM course after VDZ.